Study on Drilling Fluid Using Electrical Capacitance Tomography (ECT) - Che Ghazali, Mohd Atiqullah (Universiti Teknologi Petronas, 2011)
This paper discusses on the applications of Electrical Capacitance Tomography (ECT) system in order to develop a new technique for assessing the drilling fluid. It is widely popular and non-intrusive technique for sensing and measuring the spatial distribution, voidage, and velocities of flow in vessel or pipe. Hence, it helps the mud engineer to access the drilling mud circulation with real time monitoring inside the borehole because traditionally, data collection was acquired at the surface in the mud pit. As kick start of exploration ECT' s technique into drilling operation, this project is mainly focusing on the evaluation of drilling fluid using the ECT. The drilling fluid will be placed inside the vessel container with sensor to monitor the projected images at round pixel map based on a set condition in static condition. The findings will give better prediction of data patterns for dynamic condition of the drilling fluid.